Depression amongst caregivers of children and adolescents with perinatally acquired HIV in Cape Town, South Africa - Booysen, Gillian (Department of Psychiatry and Mental Health, 2023)
Background Depression remains the most commonly diagnosed mental health disorder. It adds significantly to the global burden of disease and is responsible for the most years of life lost to disability in both men and women (Rehm & Shield, 2019). The successful roll-out of antiretroviral therapy (ART) to those living with HIV has resulted in the emergence of an increasing population of children and adolescents with perinatally acquired-HIV (PHIV) requiring care. Caregivers of PHIV are at increased risk for the development of depression due to parental, child and socio-economic factors. Few studies have focused on the specific factors associated with caregiver depression in the context of caring for ART-treated and untreated PHIV. Aims and Objectives The aims of this cross-sectional study are to assess the prevalence of depression in caregivers of PHIV compared with caregivers of a HIV-seronegative matched control group (HC). In the HIV-impacted families, a comparison will be drawn between the prevalence of depression in biological and non-biological caregivers. Factors associated with depression in this vulnerable group will be assessed using various caregiver, child and socio-economic measures. Methods Caregivers of 75 PHIV and 30 HC were selected from a community healthcare setting in Cape Town. Results There was no difference found between levels of depression in PHIV caregivers (biological or non-biological) and caregivers of HC. Internalising and externalising child behaviours, poor family resources (including basic needs, money, time for self and time for family) and limited social support were associated with depression in both caregiver groups. In caregivers of HC, parental stress was associated with higher levels of depression. Conclusion Factors independent of HIV status of children may be driving depression in caregivers of children and adolescents in Cape Town, South Africa where HIV is endemic. Thus, this study could facilitate a better understanding of depression in the context of caring for PHIV and better inform interventions in these vulnerable family systems.